Writing differently with film: An animated video on gender, leadership, and language - Brigitte Biehl; Katerina Schönfeld (Gender, Work & Organization, 2023)
The animated video “Leadership and Discourse” (original title: “Führung und Sprache”) (4:05~min) is produced by us (a filmmaker and a scholar) and stands as an artistic research contribution that is published on the GWO website (https://bcove.video/3yBUL04). It links to and develops forms of “writing differently” in organization studies with moving images, colors, and sound. Drawing on feminist research, it visualizes how language creates a view on leadership as white, heterosexual, and masculine that excludes women and non-binary individuals, queer people, and people of color. The male leader stereotype “stands” his ground and dominates all others. The video also shows how marginalized positions may find their form when they act in solidarity, reject misogynist vocabulary and hate-speech, redefine words, and create new terms. In a way that a text cannot, the film allows viewers to experience gender and leadership as a product and artifact of discursive practices. It invites viewers to affectively relate to the content and encourages them to re-imagine ourselves and others in organizations and leadership relationships beyond binary gender stereotypes. This written article serves as an academic framing, a common standard for artistic research, offering an interpretation of the video and situating the theoretical contribution. We theorize how artistic research as “writing differently” can challenge dominant forms of knowledge production and may support learning and leadership development with alternative, reflective, and experiential approaches and materials.
Keywords: 300; artistic research; feminine writing; film; gender; leadership; leadership development